Penerapan Pembuatan Karya Kreatif Scrapbook Pada Pembelajaran Seni Budaya dan Keterampilan Kelas V SDK Cawalo-Palue - Benyamin Regi (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aimed to describe the process of making and the creative Scrapbook masterpiece of 5th grade students SDK Cawalo-Palue on SBK Subject. The type of this research is a qualitative type with descriptive method and participants observation technique. The subject of this research is 5thA students of SDK Cawalo Palue. The research instrument is human instrument, by using obsevation guidelines and interview guidelines. The results of the research were (1) The process of making four creative works of Scrapbook begins with a discussion determining the theme to be selected in making the work. Followed by ornaments that support the theme. Next, create the ornaments with drawing patterns on origami paper, cut the patterns that have been made and coloring the ornaments using color paint. Then the ornament is affixed to the background paper. (2) Four creative works of Scrapbook made by students have contained elements and principles of fine arts. Among them, in the creative work of Scrapbook has included elements of lines, colors, shades, textures, space and dark light on Scrapbook ornaments. Placement of the ornaments on paper that has met the principles of art, unity, tone, full and harmony.